(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Critical reading is not merely about comprehending words on a page but involves an active engagement with texts to analyze, question, and interpret meaning. This paper explores the role of interrogating texts as a methodological aspect of critical reading. It examines the cognitive processes involved in textual interrogation and discusses various strategies that enhance deeper comprehension. The study employs a qualitative research approach, incorporating literature review, classroom observations, and expert interviews to analyze how critical reading fosters analytical thinking, problem-solving, and independent reasoning. The findings indicate that interrogating texts improves comprehension, encourages metacognition, and enhances the ability to evaluate information critically. The paper concludes by emphasizing the necessity of fostering interrogation-based reading strategies in educational settings.